IMPLEMENTASI AKUNTANSI SOSIAL DAN LINGKUNGAN SEBAGAI TANGGUNG JAWAB SOSIAL PERUSAHAAN PADA PT. PERTAMINA (PERSERO) MARKETING OPERATION REGION II PALEMBANG - Masayu Mikial; Lailatul Qodriyah (JURNAL KOMPETITIF, 2015)
ABSTRACTÃ‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â  This study basically discusses the implementation of the Social and Environmental Accounting as a Corporate Social Responsibility at PT Pertamina (Persero) Marketing Operation Region II Palembang. The purpose of this study was to determine and analyze the implementation of the Social and Environmental Accounting as a Corporate Social Responsibility at PT Pertamina (Persero) Marketing Operation Region II Palembang.Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â  Implementation of corporate social responsibilit, Pertamina (Persero) Marketing Operation Region II Palembang can be said has been good to be divided into two usage. For the Partnership Program and Community Development made Statements of Financial Position and separate Program Activity Report with the Financial Statements of the Company. For its Corporate Social Responsibility (CSR), Pertamina (Persero) Marketing Operation Region II Palembang seen from the post Expense Community Development (ComDev) in the Income Statement are classified in the Other Expenses. PT. Pertamina (Persero) Marketing Operation Region II Palembang also reveal the activities of social responsibility that a Sustainability Report in narrative form, because it's social responsibility does not have control of the company and indeed the position is outside the company's operations, and not has a significant influence on the company for the purpose of PT. Pertamina (Persero) carry out its social responsibility is to meet the existing regulations, to improve the image, quality and productivity, reduce the cost of risk on the company's operations, lowering stress, and increase customer loyalty.Ã‚Â Keyword : Social and Environmental Accounting, Corporate Social ResponsibilityÃ‚Â